When it is time to hang up the keys: the driving and dementia toolkit – for persons with dementia (PWD) and caregivers – a practical resource - Byszewski, Anna; Aminzadeh, Faranek; Robinson, Kelly; Molnar, Frank; Dalziel, William; Man Son Hing, Malcolm; Hunt, Lynn; Marshall, Shawn (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background The aim of this project was to develop a toolkit to assist persons with dementia (PWD) and their caregivers, in planning for retirement from driving. The information gathered was used to develop a tool that can assist reflection about, and make sound decisions in this challenging area of the dementia journey. The purpose is to keep safe drivers on the road and to prepare those who are moving towards being at risk of being involved in crashes, to eventually stop driving when they are unsafe. The toolkit was prepared to address the concerns of both the PWD as well as the caregivers. Strategies and solutions are presented for both the PWD and the caregivers. A grief insert was also developed that can assist caregivers in supporting the PWD in the grief process that can accompany losing one’s driving privileges.